Fault signature analysis based on digital fault recorder in malaysia overhead line system - Asman S.H.; Ab Aziz N.F.; Abd Kadir M.Z.A.; Amirulddin U.A.U. (Institute of Electrical and Electronics Engineers Inc., 2023)
Decision making; Electric lines; Transmissions; Digital fault recorder; Fault characteristics; Fault signature; Lightning strikes; Natural disasters; Overhead transmission lines; System faults; Voltage waveforms; Disasters